ASSESSING THE IMPACT OF COGNITIVE STYLES AND CRITICAL THINKING SKILLS ON WRITING PROFICIENCY - Ramli; Kurniawan, Cilung; Dalami, Muh. Arrum; Yon A.E (English Review: Journal of English Education, 2025)
The important variables were reported to have the potential to affect the students’ performance in writing English essay. This present study investigates the predictive potential of cognitive styles and critical thinking skills variables on students’ performance in writing English essay. The quantitative design has been used in this study, wherein a multiple regression analysis was carried out between independent variables and writing skills. The total population was 40, from which a sample of 26 students was drawn based on simple random sampling from English department students of Faculty of Teacher Training and Education, Universitas Lakidende Unaaha. Concerning the results of regression analysis, it was stated that cognitive styles and critical thinking skills (p-value are respectively 0.002 and 0.021) had a significant effect on student performance in writing English essay. In other words, increasing critical thinking skill by one unit is on average associated with an increase in writing score of 2.468 points, and for an increase in cognitive style, there is a corresponding increase of 0.766 points. However, from these standardized beta coefficients, it is evident that critical thinking skills alone (0.627), have a stronger influence on writing performance than cognitive styles (0.449). The constant of 35.741 gives the predicted value of writing performance when the independent variables are zero. These findings point out how important it is to foster critical thinking and awareness of cognitive styles if an attempt is made to boost students’ performance in writing.